STATISTICS OF VARIATION RANGE OF F2- LAYER MAXIMUM HEIGHT OF THE IONOSPHERE - A.F. Yakovets; A. Jahanshir; G.I. Gordienko; B.T. Zhumabayev; Yu.G. Litvinov; N. Abdrakhmanov (Academic Scientific Journal of Computer Science, 2019)
The statistics of the nights when the ionosphere was sounded at the Institute of the Ionosphere in 2009–2016, and the nights during which the large scale traveling ionospheric disturbances (LS TIDs) were observed, were presented. Out of 1454 sessions of nighttime observations of the ionosphere, LS TIDs were observed in 185 sessions. The features of atmospheric and magnetospheric LS TIDs are found: a) high coherence of variations of critical frequencies and virtual heights (h'(t)), b) an increase in the amplitude of variations of h'(t) with an increase in the sounding frequency, c) phase delay of variations of h'(t) at lower frequencies relative to variations at high frequencies. A method has been developed for estimating the magnitude of the peak to peak variations in the height of the F-layer maximum, in terms of the range of variations of the virtual reflection height of the sounding signal h'(t) at the maximum frequency reflected from the ionosphere. Distributions of the magnitude of the maximum height variations are obtained for magnetically quiet and magnetically active observation conditions of the LS TIDs. It was found that the maximum probabilities of the magnitude of peak to peak lie in the range of 40-50 km for a disturbed and 30-50 km for a quiet magnetic field.